Transitions are dangerous : oil and the world economy, 1990 - Turk, J (Oxford Institute for Energy Studies, 1990)
For the last twenty years, oil has probably been the single most important economic commodity. Its only competitor, with the exception of money itself, has perhaps been the microchip. Oil has the greatest share of world trade, provides the mainstay of the worlds largest companies, is the dominant force in the determination of energy prices – and has now played a major part in bringing about international conflict – the First Oil War. The leverage of oil over almost every aspect of economic life results from the combination of its great importance to all economies and the concentration of low-cost oil resources in a limited and unstable part of the world. Consequently, it is inevitably a “political commodity”.